Genetic and structural characterisation of 20 autosomal STR loci from the Henan Han population of Central China - Wu, Hongyan; Wang, Kejie; Zhang, Lin; Fan, Aiying (Annals of human biology, 2022)
Aim: This study was designed to investigate the genetic polymorphisms and forensic parameters of the 20 autosomal short tandem repeat (STR) loci included in the PowerPlex ® 21 System (Promega, USA) in the Henan Han population with a view to expand the genetic information available for this population in human genome databases. Subjects and methods: We evaluated the genetic polymorphisms from 20 autosomal STR loci using DNA typing based on 2995 individuals from the Henan Han population in Central China and then used this information to investigate the genetic relationships between this population and 10 other Han populations across China. These comparisons included genetic distance, phylogenetic trees, and principal component analysis (PCA). Results: We identified a total of 290 alleles and 1343 genotypes within the Henan Han population, with none of these loci deviating from their Hardy-Weinberg equilibrium (HWE). The population comparisons revealed that geographically close populations demonstrated closer genetic relationships. Thus, the Henan Han population was shown to be close to both the Beijing Han and Tianjin Han populations, creating a single cluster. In addition, these 20 STR loci exhibited a high degree of genetic polymorphisms, making them suitable for individual identification and parentage testing. Conclusions: The results of this study will enrich the forensic databases of Chinese Han populations and serve as a resource for further studies in these populations.